NH4 Service development for people with HIV who have comorbid conditions using experience-based co-design methodology. (30th June 2016) - Nixon, Eileen; Cooper, Vanessa; Youssef, Elaney; Smith, Helen; Robert, Glenn; Fisher, Martin
Abstract : Background/introduction: There is a need for evidence - based models of care to effectively manage the increasing numbers of the people with HIV (PWH) who have comorbid conditions. This study was part of an NIHR Programme Development Grant to inform the development of HIV services to meet the needs of an ageing population. Aim(s)/objectives: To explore the healthcare experiences of PWH who have comorbid conditions and the staff involved in their care to identify priorities for service improvement. Methods: Experience-based co-design methodology was used to understand the experiences of PWH accessing General Practice, HIV, Cardiology, Liver, Renal and Rheumatology services. Patients were recruited from the HIV clinic and staff purposively sampled from the service areas. Experiences were gathered through observation, diaries, audio and filmed interviews. Thematic analysis was undertaken and filmed patient interviews analysed for emotional touchpoints. Staff and patient feedback events were utilised to validate data and identify areas for service development. A joint staff and patient co-design event was held to agree shared priorities for future services. Results: 22 patients (with 110 comorbidities) and 18 staff were recruited. A composite film was produced from the patient interviews. Examples of touchpoints were communication, burden of appointments and repetition across services. Patients identified 6 areas for service improvement and staff identified 3. The agreed priorities for future service development were care co-ordination, shared medical records/results and systems to manage multiple appointments. Discussion/conclusion: Experience-based co-design methodology was effective in identifying future service models for PWH who have comorbid conditions.